AHR gene-dioxin interactions and birthweight in the Seveso Second Generation Health Study. (14th August 2018) - Ames, Jennifer; Warner, Marcella; Mocarelli, Paolo; Brambilla, Paolo; Signorini, Stefano; Siracusa, Claudia; Huen, Karen; Holland, Nina; Eskenazi, Brenda
Abstract: Background: 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) is proposed to interfere with fetal growth via altered activity of the aryl hydrocarbon receptor (protein: AHR; gene: AHR ) pathway which regulates diverse biological and developmental processes including xenobiotic metabolism. Genetic variation in AHR is an important driver of susceptibility to low birthweight in children exposed to prenatal smoking, but less is known about these genetic interactions with TCDD, AHR's most potent xenobiotic ligand. Methods: The Seveso Women's Health Study (SWHS), initiated in 1996, is a cohort of 981 Italian women exposed to TCDD from an industrial explosion in July 1976. We measured TCDD concentrations in maternal serum collected close to the time of the accident. In 2008 and 2014, we followed up the SWHS cohort and collected data on birth outcomes of SWHS women with post-accident pregnancies. We genotyped 19 single nucleotide polymorphisms (SNPs) in AHR among the 574 SWHS mothers. Results: Among 901 singleton births, neither SNPs nor TCDD exposure alone were significantly associated with birthweight. However, we found six individual SNPs in AHR which adversely modified the association between maternal TCDD and birthweight, implicating gene-environment interaction. We saw an even stronger susceptibility to TCDD due to interaction when we examined the joint contribution of these SNPs in a risk allele score. These SNPs were all located in noncoding regions of AHR, particularly in proximity to the promoter. Conclusions: This is the first study to demonstrate that genetic variation across the maternal AHR gene may shape fetal susceptibilities to TCDD exposure.